2019
DOI: 10.1590/1807-2577.06419
|View full text |Cite
|
Sign up to set email alerts
|

Effect of techniques, trays and materials on accuracy of impressions clinically made

Abstract: Introduction Making accurate and dimensionally stable impressions to duplicate oral conditions and tooth morphology is an essential step of prosthetic dentistry for fabricating well-fitted indirect restorations and, consequently, ensure the longevity and success of the treatment. Several authors describe pros and cons of different impression techniques, although there is no unanimity among them about the best one. Objective This study evaluated casts’ accuracy made by different impression techniques, trays an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The results showed, as in Table (1), that there were changes in the linear dimensions in all groups, regardless of the type of water used, but unevenly between them without the presence of statistically signi cant differences, where the value of the signi cance level was greater than 0.05 in most of the measurements, except for the front vertical linear dimension where The signi cance level value was less than 0.05, meaning that there are statistically signi cant differences in all groups Whatever type of water is used. To nd out which groups contain the largest values of the differences, the Bonferroni method was used, which showed that the changes in the tap water group were the largest, where the p-value was less than 0.05, that is, at the 95% con dence level, there are statistically signi cant differences, as in table (2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed, as in Table (1), that there were changes in the linear dimensions in all groups, regardless of the type of water used, but unevenly between them without the presence of statistically signi cant differences, where the value of the signi cance level was greater than 0.05 in most of the measurements, except for the front vertical linear dimension where The signi cance level value was less than 0.05, meaning that there are statistically signi cant differences in all groups Whatever type of water is used. To nd out which groups contain the largest values of the differences, the Bonferroni method was used, which showed that the changes in the tap water group were the largest, where the p-value was less than 0.05, that is, at the 95% con dence level, there are statistically signi cant differences, as in table (2).…”
Section: Resultsmentioning
confidence: 99%
“…Recording an accurate impression is one of the most important steps in prosthetic dentistry for a successful denture, Therefore, it is important to fully understand its characteristics and the factors that in uence it to avoid possible complications 1,2,3,4 . Alginate was developed as an alternative to agar during World War II, and is still the rst choice for primary impressions of edentulous patients also can be used to record diagnostic impressions of orthodontic treatment, or to obtain the nal gypsum cast in cases of partially edentulous patients where obtaining accurate nal impression is an important rst step For a series of subsequent steps to achieve a good oral prosthetics 5,6,7,8 .…”
Section: Introductionmentioning
confidence: 99%
“… 24 , 25 Moreover, the accuracy of the two-step technique using uniform wash space 11 , 20 was more than the one-step technique. 28 , 29 , 41 Another disadvantage of the one-step technique is that the margins may be recorded in putty rather than light body because of the lower viscosity of the latter, which can result in inaccurate dies. 9 , 20…”
Section: Discussionmentioning
confidence: 99%